Motiv och avkastningsvärde vid köp av skogsfastigheter : en intervjuundersökning - Jonsson, Arvid (SLU/Dept. of Forest Resource Management, 2008)
The purpose of this paper has been to find out what motives buyers of forest property has for there purchasse, what competence they have in economics and forestry, and what analysis they had done before the purchase. The study is based on interviews with nine different buyers from two geographical areas, five from Hälsingland and four from Småland/Skåne. A forest property is a property where the value to 100 % consist of forest. A part from the interviews every purhase has been analysed in comparison to an estimation of the yield value. The theoretical yield value was estimated with a computer programme. The calculation is based on for time of the study relevant information about prices, costs and interests.